2017
DOI: 10.3233/jcb-15030
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and cultivation of primary keratinocytes from piglet skin for compartmentalized co-culture with dorsal root ganglion neurons

Abstract: Abstract. Keratinocytes are the main cell population in the epidermis, where they coexist with a variety of other cell types. Their successful isolation and cultivation have afforded opportunities to study epidermal functions. Human keratinocytes have been studied most extensively, but their source is limited by the skin supply. In a previous work, we developed an in vitro co-culture model of porcine keratinocytes with porcine sensory neurites to investigate functional interaction. However, a detailed descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…One explanation that may account for this observation involves the specific requirements for an optimal cell culture of pKERs in terms of culture media composition and coating substrates. A recent study by Ponce et al, in which several culture media and adhesion substrates were examined, clearly demonstrates that media rich in hormones and specific growth factors together with the collagen-based matrix used to cover growth surface are necessary for the effective cultivation of keratinocytes isolated from the skin of newborn piglets [ 47 ]. In light of these findings, we cannot exclude that in our study, although CMs were rich in VEGF, bFGF, and MCP-1, they did not contain the full package of factors necessary for supporting pKERs’ migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation that may account for this observation involves the specific requirements for an optimal cell culture of pKERs in terms of culture media composition and coating substrates. A recent study by Ponce et al, in which several culture media and adhesion substrates were examined, clearly demonstrates that media rich in hormones and specific growth factors together with the collagen-based matrix used to cover growth surface are necessary for the effective cultivation of keratinocytes isolated from the skin of newborn piglets [ 47 ]. In light of these findings, we cannot exclude that in our study, although CMs were rich in VEGF, bFGF, and MCP-1, they did not contain the full package of factors necessary for supporting pKERs’ migration.…”
Section: Discussionmentioning
confidence: 99%
“…Skin samples were sliced using a dermatome (Zimmer ® Electric Dermatome; Zimmer Biomet Surgical, Inc., Dover, OH, USA). Skin layers were incubated in 1.6 U/mL dispase (Gibco, Life Technologies Corporation, Grand Island, NY, USA) overnight at 4 °C to separate the epidermis from dermis [ 47 ]. The next day, the separated epidermis was digested for 3 min in 0.05% trypsin-EDTA solution (Sigma-Aldrich Co., St. Louis, MO, USA) and filtered through 70-μm strainers (Corning Incorporated, NY, USA) for keratinocyte isolation.…”
Section: Methodsmentioning
confidence: 99%
“…45,57 Despite this knowledge, the majority of in vitro DRG platforms utilize 2D culture, as represented in Table 1. [23][24][25]45 Commonly, the methods of 2D DRG culture include direct plating onto a rigid surface or onto a coating of varying substrate stiffness. 39,[62][63][64][65][66] However, in 3D culture, cells are embedded within a matrix where the mechanical properties are tunable by modifying the composition.…”
Section: Three-dimensional Environmentmentioning
confidence: 99%
“…Specifically, previous work has shown that the stiffness of the culture environment influences axonal growth, 59,60 branching, 61 and neuronal excitability of DRGs 45,57 . Despite this knowledge, the majority of in vitro DRG platforms utilize 2D culture, as represented in Table 1 23–25,45 . Commonly, the methods of 2D DRG culture include direct plating onto a rigid surface or onto a coating of varying substrate stiffness 39,62–66 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation